A Cross-Linked Poly(Ethylene Oxide)-Based Electrolyte for All-Solid-State Lithium Metal Batteries With Long Cycling Stability - Xin, Chengzhou; Wen, Kaihua; Guan, Shundong; Xue, Chuanjiao; Wu, Xinbin; Li, Liangliang; Nan, Ce-Wen (Frontiers in Materials, 2022)
A cross-linked poly(ethylene oxide) (PEO)-based electrolyte with polyaryl polymethylene isocyanate (PAPI) as the cross-linking agent is synthesized by a facile one-pot reaction. The PEO chains are cross-linked by PAPI through the reaction between hydroxyl groups (-OH) and isocyanate groups (-N=C=O). The effects of PAPI on the electrochemical performance of the PEO-based electrolyte and the stability of the electrolyte/electrode interface are investigated. The PEO-PAPI electrolyte has an ionic conductivity of 9.3×10-5 - 1.3×10-4 S cm-1 at 60 C. The cross-linked PEO-PAPI electrolyte exhibits enhanced mechanical properties compared to pristine PEO and shows good compatibility with a lithium (Li) metal anode. An all-solid-state Li metal battery (ASSLMB) with the optimized PEO-PAPI electrolyte and a LiFePO4 cathode (1.62 mg cm-2 in mass loading) shows a discharge capacity of 112.8 mAh g-1 after 700 cycles with a current density of 88 uA cm-2 at 60 C. Even with a high mass loading of 8.4 mg cm-2, the ASSLMB with the cross-linked PEO-based electrolyte shows good cycle performance. The experimental data show that the cross-linked PEO-PAPI electrolyte is a promising candidate for solid electrolytes used in ASSLMBs.